Network Perimeter Security: Building Defense In-Depth - Riggs, Cliff (CRC Press, 2009)
Today's network administrators are fully aware of the importance of security; unfortunately, they have neither the time nor the resources to be full-time InfoSec experts. Oftentimes quick, temporary security fixes are the most that can be expected. The majority of security books on the market are also of little help. They are either targeted toward individuals pursuing security certifications or toward those interested in hacker methods. These overly detailed volumes fail to deliver the easily referenced tactical information needed to provide maximum security within the constraints of time and budget.